KOMITMEN PNS TERHADAP ORGANISASI DI REKTORAT UNIVERSITAS NEGERI YOGYAKARTA - Agus Wahyuadianto (Widyariset, 2010)
As the back bone of government, civil servant plays important role on delivering civil service. Therefore, it needs strong organizational commitment to guarantee the service given. Allen and Meyer developed model to measure organizational commitment, called the three- omponents model. As shown in the name, the model contained three components, i.e.: (1) affective commitment; (2) continuance commitment; and (3) normative commitment. This was a report from a study aimed to measure organizational commitment among civil servants in Main Office of Yogyakarta National University (Universitas Negeri Yogyakarta) Indonesia. It applied quantitative-descriptive in research method. The survey was held in 2004 and used a questionnaire from Allen and Meyer. It took 105 respondents and the result was 58 persons (or 55%) showed average middle mild organizational commitment, 27% showed strong organizational commitment, and 18% of them showed weak commitment.